Analysis of middle semester exam subjects for Automotive Vehicle Chassis (AVC) to improve the implementation management of learning evaluation - Umaroh, Susi Tri; Soeryanto, Soeryanto; Warju, Warju; Marniati, Marniati (Jurnal Pendidikan Vokasi, 2022)
Entering the 21st century with the industrial revolution 4.0, the speed of progress in information and communication technology has become unstoppable. One of the most benefited from these advances in the world of education. Exploration of learning resources, and discussion forums, for the evaluation of learning can be done easily because of technological advances. Learning evaluation can use a digital platform, and it is very easy to analyze to improve the management of the implementation of learning evaluation. This study was conducted to analyze the mid-semester test instrument, which includes Higher Order Thinking Skills (HOTS) questions and is used to measure students' abilities in the subject of Automotive Vehicle Chassis (AVC) in the Department of Automotive Engineering) at SMK Dharma Bahari Surabaya, Indonesia. This research method is descriptive and quantitative. The sample in this study was 40 students. The mid-semester questions were given as many as 40 questions related to the mid-semester exam material using the Quizizz platform. Analysis of the items is carried out by using the Rasch model approach to obtain fit items. This analysis was carried out with the help of Winsteps 3.73 software. In this study, it was found that the instrument of the question that Person Reliability at mid-semester Automotive Vehicle Chassis (AVC) was 0.85 while item reliability was 0.86. The magnitude of Cronbach's Alpha is 0.86, so it can be used to evaluate learning in AVC subjects according to the Rasch model.